KONSEP QAWWAMAH DAN KEADILAN GENDER DALAM SURAH AN-NISA AYAT 34: TELAAH TAFSIR MAQASIDI IBNU ASHUR - Dwi Sutrisno, Ahmad; Nurrohim, Ahmad; Nugroho, Kharis; Abdul Hafid, Ruhyan (LPPM STAI Muhammadiyah Probolinggo, 2025)
Surah An-Nisa' verse 34 is one of the most discussed verses in the discourse of gender relations in Islam. This verse is often in the spotlight because it is considered to legitimize the dominance of men over women in domestic relations. However, a purely textual approach without considering maqasid al-shari'ah has the potential to give birth to a biased understanding that is not in line with the principles of Islamic justice. This research aims to find out the concept of Qawwamah and gender justice according to Ibn 'Ashur through his monumental work at-Tahrir wa at-Tanwir which offers a tafsir approach oriented to maqasid al-shari'ah. By prioritizing the goals of sharia such as justice, welfare, and the protection of human rights, the tafsir maqasidi of Ibn 'Ashur can provide an alternative reading of controversial verses, including Surah An-Nisa' verse 34. This research uses a qualitative method with a thematic interpretation and maqasidi approach. The results of the study show that Ibn 'Ashur emphasized the importance of considering the social context and purpose of the shari'ah in understanding the verse. He interprets qawwamah as a form of functional responsibility, not absolute superiority. Thus, the maqasidi interpretation is able to offer a more equitable, inclusive, and relevant understanding of the principle of gender equality in Islam.